Awakening Debate And Scholarship - New Sunday Times, (2008)
AMENDMENTS to The Universities and University Colleges Act 1971 should be carried out promptly to prevent groups from politicising the matter, said Higher Education Minister Datuk Seri Khaled Nordin recently.